2016
DOI: 10.1159/000442764
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemic Hypoglycemia after Bariatric Surgery: Diagnosis and Management Experience from a Spanish Multicenter Registry

Abstract: Background: Severe postprandial hypoglycemia after bariatric surgery is a rare but invalidating complication. Our aim was to describe the different tests performed for its diagnosis and their outcomes as well as the response to the prescribed pharmacological and surgical treatments. Methods: Multicenter, retrospective systematic review of cases with recurrent severe postprandial hypoglycemia. Results: Over 11 years of follow-up, 22 patients were identified. The test most used to provoke hypoglycemia was the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 38 publications
1
36
0
2
Order By: Relevance
“…Acarbose is an α‐glycosidase hydrolase inhibitor that slows carbohydrate digestion in the small intestine, thus blunting postprandial hyperglycemia and subsequent hypoglycemia. Several small studies demonstrated that acarbose improved glucose tolerance, reduced GI hormone release, reduced the incidence of hypoglycemia and improved symptoms in patients with dumping syndrome (Table ) . However, the use of acarbose as a treatment approach for dumping syndrome is limited by the fact that it affects only late dumping symptoms and may result in side effects related to carbohydrate maldigestion, such as bloating, flatulence and diarrhoea.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Acarbose is an α‐glycosidase hydrolase inhibitor that slows carbohydrate digestion in the small intestine, thus blunting postprandial hyperglycemia and subsequent hypoglycemia. Several small studies demonstrated that acarbose improved glucose tolerance, reduced GI hormone release, reduced the incidence of hypoglycemia and improved symptoms in patients with dumping syndrome (Table ) . However, the use of acarbose as a treatment approach for dumping syndrome is limited by the fact that it affects only late dumping symptoms and may result in side effects related to carbohydrate maldigestion, such as bloating, flatulence and diarrhoea.…”
Section: Treatmentmentioning
confidence: 99%
“…Somatostatin inhibition of GLP‐1 secretion is mediated via activation of the somatostatin receptor subtype (sst) 5, with a lesser effect through sst2 . Both short‐acting and long‐acting formulations of somatostatin analogues have demonstrated efficacy by slowing gastric emptying, improving hypoglycemia and reducing early and late dumping symptoms (Table ) .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoglycemia is an increasingly recognized complication of bariatric surgery, occurring after both roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (SG) [15]. Post-bariatric hypoglycemia (PBH) typically occurs one to three hours after meals, with increased severity after intake of high glycemic index carbohydrates [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, several other cases have been reported [2]. Pancreatectomy is an acceptable treatment for this condition [13]. We aim to present a video of a case of near-total distal robotic pancreactectomy for the treatment of nesidioblastosis after Roux-en-Y gastric bypass.…”
Section: Introductionmentioning
confidence: 99%